An Antilock Braking-Guided Steering Mathematical Modelling with Integrated Automatic Control in Vehicles and Its Evaluation - Wisnujati, Andika; Hsing-Chung Chen; Widodo, Agung Mulyo; Chi-Wen Lung (International Journal of Integrated Engineering, 2025)
In the cars industry, to control slip rate from wheels and help drivers to avoid accidents on road, an integrated antilock braking and guided steering (AB-GS) system has been developed for vehicles especially cars. The brake and steering system are devices to slow down or stop the movement of the wheels on the vehicle and have ease of control and directional stability. Because the wheels are slowed down, the vehicle’s motion automatically slows down. The lost kinetic energy is con-verted into heat due to friction. The three purposes of the AB-GS brake controller are to reduce stopping time, limit slip ratio, and improve control system performance (by reducing time ratio and overshoot). For that, we build a model based on the equations of motion, which are affected by forces and moments for each axis. In the ABS system, there is an influence of force or moment towards the lateral (X), longitudinal (Y), and vertical (Z) axes. At the time of braking, there will be a change in directional force (X, Y, and Z) as well as moments that affect the direction of rolling motion, yaw and pitching. So, when you hit the brakes hard, it’s just as important to keep the vehicle stable and make sure you can steer it as it is to stop quickly. We don’t take into account changes in motion along the Z axis or moments that affect yawing and rolling. Then, from the system’s equations of motion, we can control it using PID control. By controlling the system, it is expected to prevent the vehicle from experiencing sudden locking, which can result in overturning. In this research, control performance was also tested using PID, which can improve vehicle driving ability, safety, and operating stability. To fully maintain vehicle direction stability, its integration with other control systems is needed. Simulation results validating the integrated antilock-braking and steering system not only obtain better optimal braking distances and excellent predictability but also show that the integrated control system outperforms the stand-alone braking and steering system.